2021
DOI: 10.1002/pros.24179
|View full text |Cite
|
Sign up to set email alerts
|

Impact of median lobe on urinary function after robotic prostatectomy

Abstract: Background: Enlarged median lobes (ML) can be technically challenging, particularly during bladder-neck dissection, and may affect urinary functional outcomes of robotic radical prostatectomy (RARP). If known, the impact of potentially larger bladder necks on continence and chronic obstruction on postoperative urinary symptoms might aid patient counseling. We assessed the impact of intraoperatively identified median lobes (ML) on urinary function.Methods: We reviewed our prospective RP database from 2013 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Regarding urinary continence, we depicted similar outcomes between both groups during the follow-up period. This comes in agreement with recently published data [23] . However, other reports confirmed that the presence of a PML adversely impacts continence rates [12] , [24] , [25] .…”
Section: Discussionsupporting
confidence: 94%
“…Regarding urinary continence, we depicted similar outcomes between both groups during the follow-up period. This comes in agreement with recently published data [23] . However, other reports confirmed that the presence of a PML adversely impacts continence rates [12] , [24] , [25] .…”
Section: Discussionsupporting
confidence: 94%